Representasi Body Shaming Terhadap Perempuan Berkulit Gelap Dalam Iklan Wardah Di Youtube - Ema Nayla Zalianty; Cicilia Levina Putri Jelita; Khafka Adnin Nafiza Azzahra; Saphira Christi Adipati Ginting (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This research aims to critically analyze the representation of body shaming towards dark-skinned women in Wardah's cosmetics advertisement that aired on the YouTube platform, using the Norman Fairclough model Critical Discourse Analysis (AWK) approach. This approach is used to explore the power relationship hidden behind text and visuals, as well as how discursive practices in advertising also reproduce certain social structures, especially in the context of women's beauty construction in Indonesia. Through observation of a number of Wardah advertisements, a representation pattern was found that consistently highlights bright skin color as an ideal symbol of beauty, purity, and social success. On the other hand, dark skin is not shown explicitly as something negative, but is implicitly associated with deficiencies that need to be fixed through the use of whitening or skin brightening products. An advertising narrative that implies that the transformation of the skin from dark to light is a process towards a better version of the self, indirectly strengthens the ideology of discriminatory skin color, or known as colorism. This bias is not only symbolically detrimental, but also constructs the public perception that the dominant standard of beauty can only be achieved by moving away from the dark skin identity. This kind of representation has an impact on the marginalization of dark-skinned women, who often do not get space in mainstream media or are only shown as figures who have undergone changes towards "ideal bright skin". Through analysis of texts, discourse practices, and socio-cultural practices as modeled by Fairclough, this study shows that Wardah's advertisements play a role in reproducing hegemonic discourse on homogeneous and exclusive beauty. This discourse construction does not stand alone, but is closely related to broader social structures, such as beauty industry capitalism, colonialism legacy, and patriarchal gender norms. In other words, advertising not only functions as a product promotion tool, but also as an ideological medium that shapes and maintains symbolic inequality in society. This study emphasizes the importance of applying representation ethics in the advertising industry, especially in cosmetic products that target an audience of Indonesian women who are very diverse in terms of skin color, cultural background, and social identity. An inclusive and sensitive approach to diversity is needed, so that the media is no longer a means of normalizing skin color-based discrimination, but a space that celebrates diversity and promotes symbolic equality.